Bruch's membrane pathology: A mechanistic perspective. Issue 6 (November 2020) - Murali, Aishwarya; Krishnakumar, Subramanian; Subramanian, Anuradha; Parameswaran, Sowmya
Bruch's membrane, an extracellular matrix located between the retinal pigment epithelium and the choroid, plays a vital role as structural and functional support to the retinal pigment epithelium. Dysfunction of Bruch's membrane in both age-related macular degeneration and other ocular diseases is caused mostly by extracellular matrix degeneration, deposit formation, and angiogenesis. Although these factors are dealt in greater detail with respect to the cells that are degenerated such as the retinal pigment epithelium and the endothelial cells, the pathology involving the Bruch's membrane is often underrated. Since in most of the macular degenerations early degenerative changes are also observed in the Bruch's membrane, addressing only the cellular component without the underlying membrane will not yield an ideal clinical benefit. This review aims to discuss the factors and the mechanisms affecting the integrity of the Bruch's membrane, which would aid in developing an effective therapy for these pathologies.